Interference Reduction in a Dynamic Spectrum Sharing Technique using Eigenvalue Detector Over Kapa-Mu Shadow Fading Channel - Issa, W. A.; Ojo, S. I.; Abolade, R. O.; Oyedokun, O. O.; Fawole, A. O. (Transactions on Engineering and Computing Sciences, 2025)
Wireless communication systems are crucial for modern telecommunications and expected to be a key in national development. However, the systems often don’t fully use the available radio spectrum due to traditional fixed spectrum, making the frequency spectrum a valuable yet limited resources. Dynamic Overlay and Underlay Spectrum Sharing (D-OUSS) used to address the problem suffered from high interference due to inadequate switching between the overlay and underlay spectrum sharing. Hence, in this paper, interference reduction in D-OUSS was carried out using Eigenvalue Detector (EVD). The energy detector in the existing D-OUSS technique was replaced with EVD to improve the accurate detection of white and brown spaces. The received signals, over kappa-mu shadow fading channel, were used to form covariance matrix to determine the ratio of maximum to minimum eigenvalues and used as test statistics to identify the presence of white and brown spaces. The proposed spectrum management system switches to overlay approach when white space is present, and instantly switches to underlay approach when there is presence of brown space. The proposed D-OUSS technique improved the performance of the existing D-OUSS technique with reduced interference and increased throughput.